Fluorescence study of the interaction between metal ions and methyl methacrylate methacrylic acid copolymers in aqueous solutions: thallium(I), calcium(II), and terbium(III) - Tiera, M. J.; De Oliveira, V. A.; Burrows, H. D.; Miguel, MDG; Neumann, M. G. (Springer, 1998)
The binding of the cations thallium(I), calcium(II) and terbium(III) to methyl methacrylate-methacrylic acid copolymers with different fractions of acid groups (x) has been studied in aqueous solution at, various pH values using the fluorescence of covalently bonded 9-vinyl anthracene as a probe. In all cases, the extent of binding increases as a function of the charge of the polymer with either increasing fraction of carboxylic acids or of pH. However, differences are observed in the behavior of the three cations, With Tl(I), quenching of the anthracene group fluorescence is observed. indicating that the thallium(I) approaches the probe and suggesting that the alkylanthracene is probably in a relatively polar region. Binding constants have been determined from anthracene quenching data and from studies with the fluorescent-probe sodium pyrenetetrasulfonate, Good agreement is obtained between the two methods, and values for the binding constants increase from 250 to 950 M-1 as x increases from 0.39 to 1. It is suggested that the cation is held in the polyelectrolyte domain, partly by Debye-Huckel effects and partly by more specific interactions. Stronger binding is found with calcium(II) and terbium(III), and in this case increases in fluorescence intensity are observed on complexation due to the anthracene group being in a more hydrophobic region, probably as a result of conformational changes in the polymer chain. In the former case the stoichiometry of the interaction was determined from the fluorescence data to involve two carboxylate groups bound per calcium. Association constants were found using murexide as an indicator of free calcium to vary from 8400 to 37 000 M-1 as x increases from 0.39 to 1. It is suggested that in this case specific calcium(II)-carboxylate interactions contribute to the binding. With terbium(III), a greater increase in the probe fluorescence intensity was observed than with calcium, and it is suggested that the interaction with the polymer is even stronger, leading to a more pronounced conformational change in the polymer. It is proposed that the terbium(III) interacts with sis carboxylic groups on the polymer chain, with three being coordinated and three attracted by electrostatic interactions.
Keywords: polyelectrolytes; metal/polyelectrolyte interactions; polyelectrolyte conformations